The value and risk of human capital - Luca Benzoni; Olena Chyruk (Federal Reserve Bank of Chicago, 2015)
Human capital embodies the knowledge, skills, health, and values that contribute to making people productive. These qualities, however, are hard to measure, and quantitative studies of human capital are typically based on the valuation of the lifetime income that a person generates in the labor market. This article surveys the theoretical and empirical literature that models a worker's life-cycle earnings and identifies appropriate discount rates to translate those cash flows into a certainty equivalent of wealth. The chapter begins with an overview of a stylized model of human capital valuation with exogenous labor income. We then discuss extensions to this framework that study the underlying economic sources of labor income shocks, the choices, such as work, leisure, retirement, and investment in education, that people make over their life, and their implications for human capital valuation and risk.
Keywords: 330